TURKI USMANI DAN POLITIK HUKUMNYA - Abd. Mukhsin (State Islamic University North Sumatra, 2009)
Abstrac : The survival of the Ottoman Empire for more than six hundred years (1281-1924 M) with its various weaknesses and advancement had a great contribution to the Islamic history. The empire centered in Istanbul but encompassing major portions of North Africa, the Arab world and Eastern Europe. This article concentrates on highlighting Siyâsah al-Syar’iyyah of the OttomanEmpire. This particularly relates to codification and legislation, the development of court system, law reform and the transfer of the power from khilâfah to republic.Kata kunci: tanzimat, peradilan, hukum, sekularisasi